ICP-MS-based quantitative analysis and risk assessment of metal(loid)s in fish species from Chennai, India - Suryapratap Ray; Chitra Jangid; Gracy Anu Francis; Sumit Sudhir Pathak; Pooja Chavan; Rahul Vashishth (Frontiers in Public Health, 2025)
IntroductionPresence of heavy metal pollutants indicates an alarming situation that disrupts marine trophic dynamics, presenting substantial threats to fish populations and ultimately affecting human societies that depend on these aquatic resources for sustainable nutrition.MethodsThe present study focused on three fish species from Chennai (Tamil Nadu, India), namely Nemipterus japonicus, Oreochromis mossambicus, and Lates calcarifer. Heavy metal profiling was conducted on organs such as liver, gills, and muscle tissue. ICP-MS was utilized to determine the concentrations of heavy metals.ResultsUpon analysis of Arsenic (As), Cadmium (Cd), Chromium (Cr), Mercury (Hg), Lead (Pb), Strontium (Sr), and Vanadium (V), the concentration ranges (dry weight) were observed as 0.044–0.096 μg/kg, 0.696–0.778 μg/kg, 5.259–12.399 μg/kg, 0.020–0.660 μg/kg, 15.400–17.649 μg/kg, 1.068–15.200 μg/kg, and 0.150–1.208 μg/kg, respectively, across the three fish species. The muscle tissues of Oreochromis mossambicus exhibited the highest heavy metal contamination, particularly due to its elevated Chromium (Cr) concentration of 12.399 μg/kg.DiscussionOreochromis mossambicus recorded the highest Hazard Index (HI) in both children (0.238) and adults (0.136). However, the HQ and HI values were < 1, suggesting that consumption of these fish species remains within a safe limit regarding heavy metal contamination. These findings underscore the need for strict monitoring and regulatory measures to reduce further heavy metal contamination in seafood.